ETIKA BERPAKAIAN DALAM ISLAM (Studi Tematik Akhlak Berpakaian Pada Kitab Shahih Bukhori) - Aguskhunaifi, Titikrahmawati (INSPIRASI (Jurnal Kajian dan Penelitian Pendidikan Islam), 2019)
The background of this research is based on the reality of the debate about clothing in Islam that has never been over from the aspect of fiqh, while the moral aspect or the value of dress itself is rarely discussed. The focus of the question is how is the Islamic concept of dress ethics in the Hadith in the Shahih Bukhari Book? This type of research is literature or library research, using a historical approach that is an effort to understand the meaning of an event and its relations to humans in certain situations. In addition, it also uses a social approach, namely understanding the text by relating social events which include: 1) Bureaucratic, traditional, colonial and national changes. 2). Change in adherents; upper class, middle class or lower class. 3). Change in location, village, city and metropolitan area. 4). Change of education.Based on the search for hadith in Sahih Bukhari, it can be concluded that the concept of dress morality in Sahih Bukhari includes clothing for men and women. There are several terms used in the hadith to refer to clothing, namely for example, Gamis, Scarves, Robes, Scarves, Turban, Taqanu`, Kissa` and Kamishah. In addition to the type of clothing also includes the procedure for dressing from the order to put the right first to wear, put the left one first to let go and pray for those who wear new clothes so that blessings. The thing that is no less important is the condition of dressing itself which should not be arrogant when wearing it, it should not be excessive (tabarruj) in dressing. Moral is a value that is inherent in someone who is attached to the function of clothing itself, namely closing the aurat (something that must be covered) and the motivation to dress is not only to close physically but to cover up shame. So that the morality of dressing the foundation is because of Allah and not for luxury or human praise.